Comparison of methodologies to quantify phytate phosphorus in diets containing phytase and excreta from broilers - Naves, L de P (Asian-Australasian journal of animal sciences, 2014)
The use of a suitable methodology to quantify the phytate phosphorus (Pphy) content in both the feed and the excreta from broilers is required to enable accurate calculation of the catalytic efficiency of the phytase supplemented in the feed. This study was conducted to compare 2 analytical methodologies (colorimetry and also high-performance liquid chromatography with a refractive index detector) in order to calculate the phytase efficiency by utilizing the results from the methodology that was shown to be the most appropriate. One hundred and twenty broilers were distributed in a (4+1)×2 factorial arrangement, corresponding to 4 diets that were equally deficient in P supplemented with increasing levels of phytase (0, 750, 1,500, and 2,250 units of phytase activity - FTU - per kg of feed) plus 1 positive control diet without phytase, supplied to male and female birds. The result indicated that the colorimetric methodology with an extraction ratio of 1:20 (mass of sample in g:volume of the solvent extractor in mL) was shown to be the most adequate. There was no interaction between the phytase level and the sex of the broilers (p>0.05). Males consumed 12% more Pphy than did females (p<0.01), but the sex of the broilers did not affect (p>0.05) the excretion and retention coefficient of Pphy. The increase in the phytase level of the diet reduced (linear, p<0.01) the Pphy excretion. The greatest Pphy retention was estimated at 87.85% when the diet contained 1,950 FTU/kg (p<0.01), indicating that it is possible to reduce the inorganic P in the formulation at an amount equivalent to 87.85% of the Pphy content present in the feed, which, in this research, corresponds to a decrease in 2.86 g of P/kg of the feed